Global importance of large‐diameter trees. Issue 7 (8th May 2018) - Lutz, James A.; Furniss, Tucker J.; Johnson, Daniel J.; Davies, Stuart J.; Allen, David; Alonso, Alfonso; Anderson‐Teixeira, Kristina J.; Andrade, Ana; Baltzer, Jennifer; Becker, Kendall M. L.; Blomdahl, Erika M.; Bourg, Norman A.; et al.
Abstract: Aim: To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location: Global. Time period: Early 21st century. Major taxa studied: Woody plants. Methods: We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5, 601, 473 stems across 9, 298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results: Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2  = .62, p  < .001). Large‐diameter trees in high biomass forests represented far fewer species relative to overall forest richness ( r 2  = .45, p  < .001). Forests with more diverse large‐diameter tree communities were comprised of smaller trees ( r 2  = .33, p  < .001). Lower large‐diameter richness was associated with large‐diameter trees being individuals of more common species ( r 2  = .17, p  = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2  = .46, p  < .001), as did forest density ( r 2  = .31, p  < .001). Forest structural complexity increased with increasing absolute latitude ( r 2  = .26, p  < .001). Main conclusions: Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.